(untitled) (Scientific journal of the Fergana State University, 2023)
The article highlights the role of the defensive structures of ancient Fergana in the development of urbanization processes in Central Asia, their features and historical position on the example of the defensive system of the Dalvarzin monument of the Chust culture, which is a full-fledged city of the Late Bronze Age and Early Iron Age.